Revealing Covid 19 Effects on Malaysian Domestic Tourism Acceptance Towards Destination Competitiveness - Binti Abdullah, Fadhilahanim Aryani; Min, Lai Hui; Syukri Hamzah, Nur Azim; Shapiai, Nur Munira; Fatihah Amran, Siti Nur Azatul; Nik Muhammad, Nik Maheran; Raja Kassim, Raja Suzana (International Journal of Criminology and Sociology, 2022)
Tourism destination competitiveness has been demonstrated as one of the significant components to improve the country’s travel industry goal. This paper study the relationship of domestic tourism acceptance towards tourism destination competitiveness. The data was drawn from a sample of 227 respondents, and a simple random sampling method was used. The data were analyzed using the Statistical Package for Social Science (SPSS). The questionnaires are distributed by online survey and face to face method. Results showed that natural resources, cultural heritage, and special events had significant relationships between domestic tourism acceptance and tourism destination competitiveness in Malaysia. As an emerging tourist attraction, several measures should be considered to improve destination competitiveness while maintaining the future development of Malaysia as a tourism destination.